2021
DOI: 10.1007/s00217-021-03796-w
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and antibacterial activities with polyphenolic profiling of wild cherry, the European larch and sweet chestnut tree bark

Abstract: This study is a comparative investigation of antioxidant and antibacterial properties of tree bark extracts of three common European species, Prunus avium L., Larix decidua Mill. and Castanea sativa Mill. The bioactive compounds present in the bark were recovered in 80% aqueous ethanol using ultrasound as the green extraction method. The antioxidant potential of the extracts was assessed with multiple biochemical assays: total phenol content (TPC) expressed in gallic acid equivalent (GAE), 2,2-diphenyl-1-picry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The other fragments at m/z 119 and 151 could be attributed to the loss of the B and C rings and the loss of the A ring, respectively [ 21 ]. Naringenin and its derivatives have been previously found in different plant parts of the Prunus species [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other fragments at m/z 119 and 151 could be attributed to the loss of the B and C rings and the loss of the A ring, respectively [ 21 ]. Naringenin and its derivatives have been previously found in different plant parts of the Prunus species [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Average was determined for each tissue (n=5) for each species. The HPLC-PDA-ESI-MS/MS separation and identification of polyphenolic compounds was accomplished based on earlier works of the authors (Hofmann et al 2016;Agarwal et al 2021;Hofmann et al 2021a).…”
Section: Methodsmentioning
confidence: 99%
“…Tannins have long been overlooked because they are not bioavailable in the small intestine, but in these last years, it was demonstrated that they are degraded by the human microbiota producing small phenols that can re-enter the bloodstream as already observed for pomegranate ellagitannins. ,, Nowadays, the biological effects of phenol metabolites derived from microbiota fermentation is object of extensive studies, since several data suggest their role in mediating the benefits of polyphenols in human . The chestnut extract and/or its fractions alone or in combination with other polyphenols have shown antioxidant, antidiabetic, antiproliferative, antibacterial, and antimycotic properties and a capacity of lowering nitrosamines and mycotoxins in raw food materials and food products. , Chestnut wood tannins at low concentrations can be effective as natural food additives, providing stability during processing and extending the shelf life of wine, meat, baked products, and gelatin. Hydrolyzable tannins from chestnut and other vegetal species were proposed as potential substitutes of synthetic food preservatives due to their antioxidant and antimicrobial properties. , The availability of food grade commercial extracts of sweet chestnut wood makes them interesting candidates for this purpose. , In view of the recent increasing attention for environmental sustainability, they have also gained increasing importance as eco-friendly materials for food packaging based on biopolymers, as such, or functionalized with natural active ingredients. Sweet chestnut extracts rich in hydrolyzable tannins have proven their effectiveness in preventing microbial growth in food packaged with active films based on chitosan and chestnut extract. , …”
Section: Introductionmentioning
confidence: 99%